Shedding light on the moon’s influence in the reproductive activity of farm animals - Perea, Fernando P.; Perea, Mariana S.; Perea-Brugal, Miguel; Méndez, Maria S. (Frontiers in Ecology and Evolution, 2025)
The idea that the Moon influences biological rhythms has long been part of traditional knowledge, and recent scientific evidence increasingly supports its role in regulating animal behavior and physiology. This review aims to assess the influence of the lunar cycle on reproductive activity in farm animals. A total of 40 studies were analyzed, encompassing nine species of agricultural importance, including one study that evaluated four species. The findings reveal that lunar phases can affect ovulation, estrus expression, fertilization, conception rates, embryo development, parturition timing, and semen quality. These effects have been reported in both natural and assisted reproductive settings, including artificial insemination, embryo transfer, and in vitro embryo production. Although the strength and direction of lunar influences vary across species and studies, recurring patterns, particularly around the new and full moon phases, suggest that lunar rhythms may modulate reproductive physiology. This review highlights the potential role of the pineal gland and melatonin secretion as mediators of electromagnetic fluctuations associated with the lunar cycle. These subtle environmental cues may influence reproductive functions through neuroendocrine pathways. In conclusion, growing scientific interest in this topic reflects its potential significance in animal biology. Further interdisciplinary research is needed to clarify the physiological mechanisms involved and to explore the practical implications of lunar modulation of reproductive activity in livestock production systems.